Eosinophilia in an Indian Patient with Helminthic Infection Unresponsive to Albendazole and Diethylcarbamazine: An Enigmatic Case of Human Fascioliasis - Ray, Debadrita; P., Ganesh C.; Kumar, Yogendra; Dhibar, Deba Prasad; Mewara, Abhishek; De, Arka (Journal of Gastrointestinal Infections, 2024)
Human fascioliasis is a zoonosis caused by Fasciola hepatica and Fasciola gigantica. Population migration, globalization of food trade, climate change, and drug resistance are contributing to the re-emergence of Fasciola infection in several countries with increased recognition even in nonendemic regions. Helminthic infections are prevalent in India and are a common cause of eosinophilia in Indian patients who are often empirically treated with antihelminthic agents. However, human fascioliasis is rarely reported in India and does not respond to commonly used antihelminthic agents like albendazole, mebendazole, praziquantel, and diethylcarbamazine (DEC). We report a case of a young female with abdominal pain and eosinophilia who did not respond to empirical treatment with albendazole and DEC. She was diagnosed with Fasciola hepatica on endoscopic retrograde cholangiopancreatography and was treated with nitazoxanide that led to complete resolution of symptoms and normalization of eosinophil counts.
Keywords: hypereosinophilia; Fasciola hepatica; fascioliasis; trematode